Hall Effect and Mobility of n-type and p-type Germanium at Different Magnetic Fields and at Different Concentrations - Jee, Madan; Kumari, Veena; Singh, Ramnath; Prasad, Vijay; Singh, Amita (Asian Journal of Chemistry, 2010)
An experimental investigation of Hall effect and mobility of germanium crystals at different magnetic fields are reported. n-Type and p-type of germanium with different kinds of impurity and different concentrations were used. A large decrease in the magnitude of the Hall constant with increasing magnetic fields have been observed in both p-type and n-type germanium crystals. A satisfactory agreement between theory and experimental results was found.